Implementasi Strategi Catatan Terbimbing(Guided Note- Taking) Dalam Pembelajaran Pendidikan Agama Islam Sekolah Dasar Negeri 18 Putussibau Utara Kabupaten Kapuas Hulu - Hardimansyah (Fakultas Pendidikan, Universitas Sultan Muhammad Syafiuddin Sambas, 2023)
The purpose of this research is to provide an argument that implementing the guided note strategy when the teacher does not understand it, does not master the steps and is unable to create teaching materials that are in accordance with the chosen strategy will make learning not go according to expectations. This research method uses descriptive qualitative methods. The primary data sources used were Islamic Religious Education teachers and fifth grade students and secondary data was the principal of North Pesantren 18 Elementary School, Kapuas Hulu Regency. Data collection techniques use observation, interviews and documentation then data analysis using data reduction, data presentation and drawing conclusions. The results of this research found: the teacher's learning planning had prepared lesson plans and guided note taking strategies. The implementation of learning went well but was not in accordance with the guided note taking strategy steps, and the obstacles found were teachers having difficulty in making teaching materials, teachers not understanding the strategic steps, insufficient time allocation, and the teacher is too fast and lacks focus in explaining the teaching material. This research not only reveals existing problems but also proposes recommendations for developing teacher training and curriculum adjustments that can enrich the learning process in the classroom. Thus, this study contributes to efforts to improve the quality of education and more effective teaching practices, especially in the context of Islamic Religious Education.